INFORMATION-ANALYTICAL SYSTEM ASSESSMENT METHODS OF COMPLEX OBJECTS - Kozulia, T. V.; Bilova, M. O. (Radio Electronics, Computer Science, Control, 2018)
Context. Formation of information-methodical, algorithmic and software sustainable development evaluation of ecological-socio-economic different complexity systems requires the formation of an integrated system approach to solving scientific problems. Objective. Formation of methodological and information software for the evaluation of compliance state and functionality of the system object with the requirements of environmental quality from the standpoint of sustainable development, which makes it safe for the environment. Methods for evaluation the quality of the system objects with different levels of difficulty are formed into an integrated analytical system for sequential processing solutions of tasks and evaluation of monitoring data: principal component analysis, comparator identification method and cognitive modelling. Results. The analysis of common approaches to the formation of complex methodical support assessment of ecological and socio-economic systems state for the security management automation is given. The expediency of creating a methodical support system of system units quality estimation in accordance with the principles of sustainable development for decision making is grounded. Mathematical methods that provide system object security level analysis and evaluation of the research results “environment – the process – the equilibrium state of the system” are defined. Algorithmic support of system objects quality estimation and designed software are tested for solution of environmental safety problems at the level of regions and enterprises of Kharkov region. The prospects regarding the state of analyzed Kharkiv region enterprises management are identified. Conclusions. Scientific novelty is defined by the formation of the complex methodological information and software support evaluation of environmental and safety system objects of ecological and socio-economic content, introduction to the methodological basis of the system analysis of objects estimation sequence “state (the system – environment) – the process (interaction, internal control, self-organization) – state of the system”. The practical significance is to develop an information-methodological and algorithmic support a comprehensive assessment of the environmental safety of complex ecological and socio-economic facilities; informational software solutions-level status assessment of safety problems of complex objects, mismatch parameters under consideration the requirements of a balanced sustainable development of the systems of different levels of study.